A conspiracy of silence: the authorial potential of full masks in performer training, dramaturgy and audience perception in South African visual theatre - Murray, Robert Ian (Rhodes University, Faculty of Humanities, Department of Drama)
Silent Mask Theatre in South Africa has the potential to cut across linguistic divides and deliver a product that offers an intimate, unique experience for the audience as well as the actor. South Africa not only has a complicated history, but also 11 languages (12 if one counts South African Sign Language "“ SASL -, which still holds a curious position of being counted official or not), and the one that theatre-makers choose to present in gives a certain "authority" to the production. Silent masks remove the need for linguistic understanding, something necessary for more abstract thought, and focusses instead on the emotional relevance and interplay between characters. In doing so, it proves an important way to create relevance for an audience, creating a delicate dance between the Mask (character and thereby text), how the actor plays it, and then the closing of meaning through the audience experience. Thus, is created a trialogue between these elements that gives the production the opportunity to speak to the hearts and minds of the audience. Globally, the study of silent character masks is still relatively new, with proponents of it only coming to the fore in the past few years (Wilsher, 2007). Mask Theatre has grown exponentially in the UK and Europe with companies like Vamos Theatre, exploring PTSD in works like A Brave Face (2018) or death in Dead Good (2021), and Familie Flöz either on the more whimsical side like Hotel Paradiso (2011) or the more hard-hitting Infinito (2006), gaining popularity and exposure. In South Africa, there is strangely not an indigenous tradition of masks, as opposed to other parts of Africa. This is fascinating, and probably points towards a more "oral tradition" of South Africa/Africa. However, the author aims to point out the ways that the silent mask entered South African consciousness at a time where more attention was being paid to "performing objects" (Proschan, 1985), and particularly in Cape Town with the advent of the Out the Box Festival. This thesis aims to contextualise Visual Theatre and Mask Theatre in a South African context, seeing within it a movement towards a more global perspective of puppetry, material performances, and performing objects. Although "ghettoised" for a long time (Taylor, 2004), performing objects emerged and became a leading case for the primal "text" of a performance. Handspring Puppet Company, Janni Younge, and the author's company, FTH:K, became primary grounds of contestation against more conventional, text-based theatre. Starting with a reflective account of the author's journey towards masks, the thesis branches out into a reflection on its author's pedagogical praxis, and how silent masks work, before critically reflecting on and analysing his key works, such as Pictures of You (2008-2013), which deals with home invasions and grief, and Benchmarks (2011), which deals with the wave of xenophobia that hit South Africa around that time. . This were built from the ground up, working with current issues both in the author's, and the country's, mileau. In the last two decades, performing object work in South Africa has begun to flourish. This is the first thesis to investigate mask work in the country during this period. Its possibilities for Screen and Stage Acting are still being explored.
Keywords: Liezl de Kock; People with disabilities and the performing arts; Experimental theater -- South Africa; Actors Training of; Theater for deaf people -- South Africa